Effect of drip irrigation and NK fertigation on strawberry under controlled environment agriculture - JASWAL, RICHA; SANDAL, SANJEEV K.; NANDA, PRABHAKAR; KUMARI, RATNESH (Journal of Soil and Water Conservation, 2026)
Effective irrigation and fertilization are crucial for successful strawberry production. Drip irrigation is a modern technology that helps combat water scarcity in agriculture, saves water, and enhances crop productivity. This study aims to evaluate the performance of strawberry cv. Chandler under various fertigation and drip irrigation levels and investigate their effect on crop and water productivity. The study aimed to assess the impact of drip irrigation and nitrogen-potassium fertigation levels on strawberry growth and productivity under protected conditions. The treatments included three drip irrigation levels, three nitrogen-potassium (NK) fertigation levels, and a control group. Strawberry cv. Chandler was transplanted in a completely randomized design replicated thrice. The drip irrigation 1.0 (DI) and DI0.8 treatments had higher soil water content than DI0.6. The DI1.0 provided favourable soil moisture, leading to higher leaf water content, while water use efficiency was higher in DI0.6. The NK100 and NK75 treatments had better root growth, efficiency of water use, and higher marketable yields than NK50. Applying a 100% recommended dose of fertilizers via fertigation at DI0.6 increased water use efficiency and saved irrigation water. However, the maximum marketable yield was obtained with DI1.0 NK100.Soil moisture increased by 6-13% at varying depths with the help of drip irrigation. This system maintains plant turgidity and enhances root growth. Fertigation through this system reduces fertilizer usage and improves yield by 18% making the system economically viable and farmer’s friendly.